2007
DOI: 10.1677/jme.1.02170
|View full text |Cite
|
Sign up to set email alerts
|

The PROGINS polymorphism of the human progesterone receptor diminishes the response to progesterone

Abstract: The human progesterone receptor (PR) is a ligand-dependent transcription factor and two isoforms, (PRA and PRB), can be distinguished. PROGINS, a PR polymorphic variant, affects PRA and PRB and acts as a risk-modulating factor in several gynaecological disorders. Little is known about the functional consequences of this variant. Here, we characterise the properties of PROGINS with respect to transcription, mRNA maturation, protein activity and proliferation. PROGINS is characterised by a 320 bp PV/HS-1 Alu ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 58 publications
6
94
0
2
Order By: Relevance
“…However, this finding was amongst all cell types (Akahira et al, 2000). There is also a suggestion that the PROGINS allele as defined by the V660L exon five variant (as examined in the present study) decreases overall response to progesterone which would be consistent with an increased risk of disease associated with this variant (Romano et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…However, this finding was amongst all cell types (Akahira et al, 2000). There is also a suggestion that the PROGINS allele as defined by the V660L exon five variant (as examined in the present study) decreases overall response to progesterone which would be consistent with an increased risk of disease associated with this variant (Romano et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…This polymorphic variant is also functionally relevant as presence of PROGINS in the PR affects the stability of its mRNA and the resulting protein has reduced response to progesterone [33]. To test if the PROGINS insertion may be a cause of reduced PR expression and or its activity in the infertile men, we screened for its presence in the DNA of fertile and infertile individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical and experimental evidences have indeed suggested that epigenetic defects in the sperm DNA is associated with recurrent spontaneous abortions [4,31]. Since the PR mRNA is expressed in the mature spermatozoa [37,38] and the PROGINS polymorphism is associated with defective PR transcription [11,33], we tested if the PROGINS insertion in the paternal genome has any effect on fertilization, embryo quality and pregnancy rates. However, no significant differences were noted when these parameters were compared in the group, where the male partner had PROGINS allele vs the wild type allele.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations